Biodiversity patterns of crustacean suprabenthic assemblages along an oligotrophic gradient in the bathyal Mediterranean Sea. (March 2017) - Almeida, Mariana; Frutos, Inmaculada; Tecchio, Samuele; Lampadariou, Nikolaos; Company, Joan B.; Ramirez-Llodra, Eva; Cunha, Marina R.
Abstract: Crustacean suprabenthic abundance, community structure, α-diversity (both taxonomic and trophic) and β-diversity were studied along a West-East gradient of oligotrophy in the deep Mediterranean Sea. The assemblages were sampled with a suprabenthic sledge in three regions (western, central and eastern basins) at three water depths (1200, 2000 and 3000 m) in May-June 2009. Environmental data were obtained at each sampling location including sediment properties, oceanographic variables near the seafloor and in the water column, and proxies of epipelagic productivity at the surface. Our results, concerning the crustacean component of the suprabenthos, showed complex trends in community structure and biodiversity across different spatial scales (longitudinal, bathymetric, and near-bottom distribution). A decrease in the number of species and abundance, accompanied by changes in the trophic structure of the assemblages were observed from West to East. In the eastern region the assemblages were impoverished in number of trophic guilds and trophic diversity. The West-East oligotrophic gradient was identified as the main driver in community structure as shown by the significant correlation with trophic environmental variables. Differences in community structure across regions were more marked at greater depths, while at the shallower sites assemblages were more similar. Within each basin, abundance, number of species and number of trophic groups decreased with depth, showing high turnover rates between 1200 and 2000 m depths. The small-scale (0–150 cm) vertical distribution of the suprabenthos was interpreted in relation to the species' functional traits (e.g. swimming activity, migratory behaviour, bottom dependence, feeding habits). Bottom-dependent and more mobile components of the suprabenthos were apparently responding differently to the various environmental challenges imposed by the large-scale longitudinal and bathymetric gradients. We propose that the bathyal suprabenthos in the Mediterranean Sea may be essentially modulated by environmental sorting, but while the more mobile faunal component has more efficient dispersal mechanisms, the bottom-dependent component may be affected by limited dispersal. However, this empirical interpretation has still to be proved given the important caveats of our study (e.g. typically low densities of the Mediterranean bathyal suprabenthos; limited number of samples; difficulties in standardization inherent to suprabenthic sampling operations in the deep sea). Highlights: Bathyal suprabenthic assemblages were analysed along the Mediterranean west-east gradient of oligotrophy. Differences in community structure across regions were more marked at greater depths. High species turnover was observed between 1200 and 2000 m depths. W-E impoverishment of suprabenthic assemblages was significantly correlated to surface productivity proxies. Differences in near-bottom suprabenthic structure may reflect individual species' response to large-scale environmental challenges.